PENGARUH DINAMIKA BURSA SAHAM ASING DAN MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN BURSA EFEK INDONESIA - Luthfiyah, Viviani; Djazuli, Atim (Jurnal Management Risiko dan Keuangan, 2022)
The purpose of this research is to identify the effects of the dynamics foreign stock exchange and macroeconomy on the composite stock price index of the Indonesia Stock Exchange. As macroeconomy consists of inflation, interest rate, exchange rate, and foreign exchange reserve, foreign stock exchange is observed form the stock price index of foreign countries as seen in their respective stock exchange during the period of 2016-2020. The IDX Composite fluctuates due to several factors such as macroeconomy and the economy of ASEAN countries. The population of this quantitative explanatory research is macroeconomic indicators and the composite stock price indices of ASEAN countries. Here secondary data consisting of monthly IDX Composite and monthly macroeconomic indicators released by Bank Indonesia in its website was used, which was then processed and descriptively analyzed in Statistical Product and Service Solution (SPSS). The results of the F-test indicate that simultaneous effects on the IDX Composite were found from each variable. Meanwhile, the results of the t test show that inflation, exchange rate, foreign exchange reserve, and the Philippine Stock Exchange (PSE) significantly affect the IDX Composite, while BI Rate, the Straits Times Index (STI), the Kuala Lumpur Stock Exchange.